Aplicação da fluidodinâmica computacional (CFD) e análise de acelerantes por CG/EM na investigação de incêndio - Cunha, Igor Olimpio Pazini da (2020)
Fire investigation is a complex activity that involves skill, technology, knowledge and science and aims to elucidate events related to fire, such as cause, origin, propagation, phenomena, etc. Chemical analysis to check the presence of foreign substances